Explaining unemployment developments in Europe: The role of wage-setting institutions and macroeconomic policies - Andrew Watt (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2017)
This study seeks to explain unemployment patterns in western European countries prior to the Great Recession. Criticising the standard view that good unemployment performance is primarily due to liberal labour market institutions, the argument advanced here is that different unemployment trajectories can be explained by the different ability or willingness of policymakers in the countries, at different points in time, to influence two key variables: nominal aggregate demand and nominal wages. In a mixture of theoretical and empirical analysis, the scope for, the constraints on, and the institutional and structural prerequisites for policymakers to exert influence on nominal output and wages are identified. Time series analysis suggests that countries that ensure or experience relatively stable growth of nominal output or demand and (less so) wage variables enjoy better labour market performance (especially since 1981). On the other hand, given demand/output volatility, an adaptive wage strategy might be desirable. A fuzzy set qualitative comparative analysis (fsQCA) is conducted for OECD countries for three twelve-year periods: 1970-1981, 1982-1993 and 1994-2005. Main findings include: Coordinated collective wage bargaining and flexible labour market institutions constitute functional equivalents. The former performed better in the first two periods, the latter in the third period. In the anti-inflationary struggle characterising the second period, there is strong evidence that a lack of collective wage setting was associated with particularly poor labour market performance, and somewhat weaker evidence that its presence helped deliver relatively good performance. From a longitudinal perspective monetary policies oriented towards employment are closely associated with favourable unemployment trends; cross-sectionally the picture is more complex, however. In most specifications counter-cyclical fiscal or monetary policies to stabilise demand prove favourable to labour market outcomes. Almost no systematic relationship between labour market performance and the degree of openness of an economy was found. Overall the findings of this analysis suggest that the existing literature has unjustifiably focused, in a one-sided manner, on the importance of liberal labour market institutions, while it has underplayed the role for both employment-oriented macroeconomic policies and coordinated wage-setting. – – Diese Studie unternimmt den Versuch, die Entwicklung der Arbeitslosenquoten in den westeuropäischen Ländern bis zum Ausbruch der Weltwirtschaftskrise zu erklären. Die Standardsicht, dass eine niedrige Arbeitslosenquote vor allem Resultat liberaler Arbeitsmarktinstitutionen ist, wird kritisiert. Es wird argumentiert, dass unterschiedliche Verläufe von Arbeitslosigkeit durch (auch zeitliche) Unterschiede in der strukturellen Fähigkeit oder Bereitschaft der Politiker bestimmt sind, zwei Variablen zu beeinflussen: die nominelle aggregierte Nachfrage und die Nominallöhne. In einem Mix aus theoretischer und empirischer Analyse werden Ausmaß, Grenzen und institutionelle Vorbedingungen einer politischen Beeinflussung des Entwicklungspfads dieser Variablen dargestellt. Zeitreihenanalysen legen nahe, dass Länder, in denen nominaler Output oder die Nachfrage - in geringerem Maße die Löhne - relativ stabil wachsen (vor allem seit 1981) eine erfolgreichere Arbeitsmarktentwicklung vorweisen können. Andererseits, geht man von gegebenen Schwankungen von Output/Nachfrage aus, dann könnte auch eine adaptive Lohnstrategie wünschenswert sein. Es wird eine "fuzzy set qualitative comparative analysis (fsQCA) für OECD-Länder für drei Perioden (1970-1981, 1982-1993 und 1994-2005) durchgeführt. Die wichtigsten Ergebnisse sind: Koordinierte, kollektive Lohnverhandlungen und flexible Arbeitsmarktinstitutionen, wie hier dargestellt, sind funktionale Äquivalente. In den ersten zwei Perioden war die Performanz des Ersteren, in der dritten Periode des Letzteren überlegen. Im anti-inflationären Kampf, der die zweite Zeitspanne prägt, zeigt sich, dass nur schwach koordinierte kollektive Lohnsetzung mit besonders schwachen Entwicklungen auf den nationalen Arbeitsmärkten einherging. Etwas weniger deutlich sind die Hinweise darauf, dass die Existenz von koordinierten kollektiven Verhandlungssystemen zu relativ guten Arbeitsmarktentwicklungen in dieser Periode beigetragen hat. Aus der Längsschnittperspektive ist eine beschäftigungsorientierte Geldpolitik eng verbunden mit positiven Arbeitslosigkeitstrends. Von einer Querschnittsperspektive betrachtet, ist die Erklärung über die Geldpolitik allerdings komplexer. In den meisten Spezifikationen tragen eine antizyklische Fiskal- und Geldpolitik mit dem Ziel der Nachfragestabilisierung dazu bei, die Lage auf dem Arbeitsmarkt zu verbessern. Kaum eine systematische Beziehung wird zwischen Arbeitsmarktentwicklungen und dem Grad der Offenheit einer Volkswirtschaft gefunden. Insgesamt legen die Resultate nahe, dass in der bisherigen Literatur ein ungerechtfertigter, einseitiger Fokus auf liberale Arbeitsmarktinstitutionen gelegt wird. So wurde die Bedeutung beschäftigungsorientierter makroökonomischer Politik und koordinierter Lohnsetzung heruntergespielt.
urn:nbn:de:101:1-201708024900
Keywords: 330